PERANG DAN LIYAN: KAJIAN FEMINISME EKSISTENSIALIS DALAM NOVEL LAMPUKI KARYA ARAFAT NUR - Gunawan, Dedek (Universitas Ahmad Dahlan, 2022)
This study aims to discuss the existence of women as the other in the novel Lampuki by Arafat Nur, which raises the theme of conflict in Aceh. This novel shows more of the daily life of the conflict-stricken community so that the situation and position of women can be seen more deeply, namely in the community itself. Furthermore, the analysis will focus on three female characters who represent the general situation of Acehnese women during the conflict. The theory used in this study is existentialist feminism, developed by Simone de Beauvoir. This study uses the qualitative descriptive method. The results showed that society's deeply rooted patriarchal culture is the biggest challenge preventing women from achieving freedom and actualizing themselves. Halimah and Siti viewed their status as wives. In other words, they are part of their husbands. However, the condition of women who do not have a husband is not better, such as Rukiya, who still needs men or is not independent. This lack of independence is due to the social construct that makes women always dependent on men. In Beauvoir's view, men place themselves as subjects and women as objects whose existence is to be subdued. Furthermore, the fate of marginalized women, and dependence on men, including being victims in the conflict, is the result of the objectification that occurs to them.